Lithium intercalation in the surface region of an LiNi1/3Mn1/3Co1/3O2 cathode through different crystal planes. Issue 82 (19th August 2016) - Hirayama, Masaaki; Abe, Machiko; Taminato, Sou; Araki, Yuya; Suzuki, Kota; Kanno, Ryoji
Abstract : The anisotropic stability of lithium (de)intercalation in the surface region of LiNi1/3 Co1/3 Mn1/3 O2 were clarified using epitaxial-film model electrodes with different orientations of (104), (1−18) and (003). Abstract : Epitaxial LiNi1/3 Co1/3 Mn1/3 O2 film electrodes with orientations of (104), (1−18) and (003) were fabricated on SrRuO3 /SrTiO3 by pulsed laser deposition. The films have a thickness of 23.8 to 25.0 nm and a flat surface with a roughness of approximately 2 nm, which offered a model system for clarifying the reaction plane dependencies of lithium intercalation at the LiNi1/3 Co1/3 Mn1/3 O2 surface. All reaction planes delivered reversible lithium intercalation for electrochemical charging–discharging between 3.0 V and 4.3 V ( vs. Li/Li + ). The (104) surface exhibited reversible behavior at a higher operation voltage between 3.0 V and 4.5 V, but the (1−18) and (003) planes showed fading of the discharge capacity and average discharge voltage. The anisotropic stability of the surface region indicates the importance of crystallographic facet control for the development of an LiNi1/3 Co1/3 Mn1/3 O2 cathode with high cycle stability.